Elevated circulating luteinizing hormone levels are associated with diabetic macroalbuminuria in Chinese men and postmenopausal women: A cross‐sectional study - Zhou, Yue; Shen, Liyan; Dong, Bingzi; Liu, Chuanfeng; Lv, Wenshan; Chi, Jingwei; Che, Kui; Gao, Yanyan; Wang, Yunyang; Wang, Yangang (Journal of diabetes, 2020)
Background Associations between sex hormones and diabetic vascular complications have recently been studied, but the role luteinizing hormone (LH) plays in diabetic kidney disease (DKD) remains uncertain. We aimed to investigate the relationship of LH and DKD in Chinese men and postmenopausal women with type 2 diabetes mellitus (T2DM). Methods Data were collected from 1775 T2DM men and postmenopausal women in hospital. The odds ratios (OR) and corresponding 95% confidence intervals (CI) in relation to LH quartiles were obtained by multiple logistic regression analysis. Results LH levels were significantly higher in patients with macroalbuminuria than in those with microalbuminuria, but were not higher in patients with microalbuminuria than in those with normoalbuminuria. Consistently, LH in those with an estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2 were significantly higher than in those with eGFR≥60 mL/min/1.73m2. The prevalence of macroalbuminuria was obviously increased for subjects of the fourth quartile of LH vs the first to third quartile (20.4% vs 6.2%, 8.0%, 12.2% in men; 25.3% vs 5.5%, 3.8%, 9.3% in postmenopausal women). Multivariate logistic regression demonstrated that subjects within the highest quartile of LH had higher odds of macroalbuminuria than those within the lowest quartile (OR 4.00, 95% CI, 1.87‐8.55 for men; OR 9.62, 95% CI, 3.42‐27.08 for postmenopausal women), independent of age, diabetes duration, or other metabolic factors. The area under the curve for detecting macroalbuminuria based on LH was 0.662 for men, and 0.767 for postmenopausal women. Conclusion High LH levels are positively associated with established DKD among Chinese men and postmenopausal women. Elevated LH may be a promising clinical factor for identifying established DKD. 摘要 目的 现有证据显示, 性激素水平与糖尿病血管并发症的发生、发展具有密切关系, 然而黄体生成素(LH)与糖尿病血管并发症的关系尚不明确。本回顾性横断面研究旨在探讨青岛市2型糖尿病男性和绝经后女性住院患者的血清LH水平和不同分期DKD的关系。 方法 收集2017~2019年于青岛大学附属医院住院的1 775例2型糖尿病成年男性与绝经后女性患者的临床资料数据。通过多元逻辑回归分析获得相对于LH四分位数的比值比(OR)和相应的95%置信区间(CI)。采用受试者工作特征(ROC)曲线分析LH水平对大量蛋白尿的诊断效能。 结果 大量蛋白尿患者的LH水平显著高于微量蛋白尿患者(男性P = 0.001, 绝经后女性P < 0.001), 微量蛋白尿患者的LH水平与正常蛋白尿患者间差异无统计学意义(男性P = 0.101, 绝经后女性P = 1.000); eGFR < 60 ml/min/1.73 m2患者的LH水平显著高于eGFR ≥ 60ml/min/1.73 m2患者的LH水平(P < 0.05)。LH第四个四分位数(Q4)内的受试者与第一至第三个四分位数(Q1~Q3)内的受试者相比, 大量蛋白尿发生率明显升高(男性20.4% vs. 6.2%, 8.0%, 12.2%; 绝经后女性25.3% vs. 5.5%, 3.8%, 9.3%)。多因素logistic回归分析显示, 在校正年龄、糖尿病病程、BMI、腰围、血糖、血压、血脂、血尿酸、吸烟、饮酒等因素后, Q4LH患者与Q1LH患者相比, 大量蛋白尿风险显著升高(男性OR 4.00, 95%CI 1.87~8.55, P < 0.001; 绝经后女性OR 9.62, 95%CI 3.42~27.08, P < 0.001)。血清LH 水平检测大量蛋白尿的 ROC 曲线下面积男性为 0.662, 最佳临界值为 8.985 mIU/ml; 绝经后女性为0.767, 最佳临界值为 29.635 mIU/ml。 结论 在2型糖尿病成年男性和绝经后女性中, 血清LH水平与晚期DKD发生率成正相关, 该作用独立于年龄、糖尿病病程及其他代谢紊乱因素。血清高水平的LH对于晚期DKD具有一定的诊断价值。 Highlights High luteinizing hormone (LH) levels are positively associated with established type 2 diabetic kidney disease (DKD) among Chinese men and postmenopausal women. The positive associations between LH and macroalbuminuria risk were independent of age, diabetes duration, or other metabolic factors. The increase of circulating LH may be a promising clinical factor for identifying established DKD.